2020
DOI: 10.1101/2020.10.04.20206508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher levels of serum IL-1β and TNF-α are associated with an increased probability of major depressive disorder

Abstract: Major depressive disorder (MDD) is a serious psychiatric disorder but there are no reliable risk assessment tools for this condition. The actual reason for affecting depression is still controversial. It is assumed that the dysregulated cytokines are produced due to the hyperactivation of the immune system in depression. We aimed to evaluate the possible alteration and the role of serum interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in MDD patients. The diagnostic and statistical manual of mental d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…So, people generally do not even care about finding the root cause of such an alarming rate of suicide. Mental health issues like depression, anxiety, loneliness remain undiscovered here (Das et al, 2021b; Repon et al, 2021). Therefore, victims do not realize that social media is causing this harm to them partially.…”
Section: Discussionmentioning
confidence: 99%
“…So, people generally do not even care about finding the root cause of such an alarming rate of suicide. Mental health issues like depression, anxiety, loneliness remain undiscovered here (Das et al, 2021b; Repon et al, 2021). Therefore, victims do not realize that social media is causing this harm to them partially.…”
Section: Discussionmentioning
confidence: 99%
“…Together with our enrichment in several immunologic signatures, our result indicated that MDD with insomnia is associated with a dysfunctional immune system. Accumulating evidence has suggested that MDD is linked to elevated proinflammatory cytokines such as interleukin (IL)-1, IL-6, tumor necrosis factor (TNF)-α, and chemokines [81][82][83][84]. Studies also indicated that the phase shift of IL-6 and TNF secretion is associated with chronic insomnia [85].…”
Section: Discussionmentioning
confidence: 99%
“…Despite having various proposed mechanisms of developing MDD, mounting pieces of evidence have suggested a strong association between chronic inflammatory processes and the pathophysiology of MDD (Miller et al, 2009; Nishuty et al, 2019). Recent findings in neuroscience also indicated an association between the families of immune protein-designated chemokines and many neuroimmune processes related to psychiatric illnesses, for examples, synaptic transmission, and plasticity, hindrance in the progression of neurogenesis, and neuron-glia communication (Das et al, 2020; Heinisch and Kirby, 2009; Pujol et al, 2005; Stuart and Baune, 2014). Activation of the inflammatory response system causes alterations in any of these functions that may lead to the pathogenesis of MDD (Daria et al, 2020; Islam et al, 2018b; Nishuty et al, 2019).…”
Section: Introductionmentioning
confidence: 99%